2015
DOI: 10.1016/j.jphotochem.2014.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Isovaleraldehyde degradation using UV photocatalytic and dielectric barrier discharge reactors, and their combinations

Abstract: The abatement of isovaleraldehyde present in air was carried out in UV photocatalytic and dielectric barrier discharge reactors (and their combinations) Operational parameters were studied in DBD treatment of isovaleraldehyde Coupled system provided a synergic improvement in the removal efficiency Sequence of reactors affected significantly to degradation efficiency of VOC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…It is observed that the CO formation in plasma and photocatalytic combined system, irrespective of the inlet concentration, is negligible. Similar results have also been reported for the photocatalytic removal of cyclohexane [13], trichloroethylene [11], and formaldehyde [28].…”
Section: End Products Analysissupporting
confidence: 88%
“…It is observed that the CO formation in plasma and photocatalytic combined system, irrespective of the inlet concentration, is negligible. Similar results have also been reported for the photocatalytic removal of cyclohexane [13], trichloroethylene [11], and formaldehyde [28].…”
Section: End Products Analysissupporting
confidence: 88%
“…High purification efficiency can be achieved by combining plasma-chemical and photocatalytic purification methods with the observation of a synergistic effect [17][18][19] costs [20]. In this case, radiation quanta enhance the oxidation processes due to the formation of additional active particles, such as, for example, those in the TiO 2 photocatalyst-plasma system [21,22]…”
Section: Introductionmentioning
confidence: 99%
“…This behavior could be explained by the occupation of the available active sites on the surface of the catalyst.Figure 4shows also that the removal efficiency of PPA decreases with increasing flow rate. This can be attributed to the decrease in the residence/contact time between the pollutant and the actives sites on the surface of the catalyst such as hydroxyl radicals[28][29][30]. BENZ (mmoL m -3 )…”
mentioning
confidence: 99%